Barcodes in Naming Basic Denture for Forensic Identification Needs - Barcode, Denture Base, Forensic identification (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: discipline within Forensic odontology is a part of the science of forensic medicine whichrecently demonstrated its role in the identification of victims, often confronted with various obstacles, toslow down the investigation of the identity of the victim. There are obstacles in the identification process,partly due to the incomplete identification data that can be collected, so that the identification of the remainsbecomes difficult and requires a long time to be confirmed despite obtaining good professional managementin the identification process. The American Board of Forensic Odontology shows that most identificationuses teeth based on restorations, caries, missing teeth and / or prosthetic devices such as removable denturesof the victim. The necessity of naming the removable denture as the data themselves are attached to thepatient can facilitate the identification of Purpose: Knowing how to manufacture and benefits of identitywith a barcode on the denture in the easy identification of individual Methods: this research was preexperiment with only posttest design. By using 10 Full Denture samples, the sample collection was obtainedfrom the Lemeshow Formula. The ten research samples were taken by simple random sampling. Conclusionbarcode contain identity data embedded in the denture base can be used as labeling on denture users becauseof their role in knowing the identity of individuals , and hacyl of reading barcodes are not influenced by thelength of the base submerged .